He first two are relatively easy. f(x-2) shifts it sideways (2 to the right in this case) f(x) -2 shifts it straight down (by 2)
f(2x) means replace x with 2x in the original 4(2x + 1)^2 − 3 if you factor out the 2 from the square root you get 4*sqr(2) ( x + ½)^2 - 3 which is now in the form a ( x -h)^2 + k the vertex is now at (-½, -3) (it used to be at (-1,-3) the "a" has gotten bigger, which makes the parabola "skinnier" (it goes up faster)
2•f(x) becomes 2*( 4(x + 1)2 − 3 ) = 8 (x+1)^2 -6 where is the vertex now? is this parabola fatter or skinnier than the original f(x) ?
Simplifying
P + -21 + -21 = 34 + -21
-21 + -21 + P = 34 + -21
Combine like terms: -21 + -21 = -42
-42 + P = 34 + -21
Combine like terms: 34 + -21 = 13
-42 + P = 13
Solving
-42 + P = 13
Solving for variable 'P'.
Move all terms containing P to the left, all other terms to the right.
Add '42' to each side of the equation.
-42 + 42 + P = 13 + 42
Combine like terms: -42 + 42 = 0
0 + P = 13 + 42
P = 13 + 42
Combine like terms: 13 + 42 = 55
P = 55
Simplifying
P = 55
Answer:
D
Step-by-step explanation:
they will sue for the rest of the money, because they are entitled to it if you are the cause of an accident.
Answer:
c. 24
Step-by-step explanation:
15+9=24